Use of time and value of unpaid family care work: A comparison between Italy and Poland - Francesca Francavilla; Gianna Claudia Giannelli; Gabriela Grotkowska; Mieczyslaw W. Socha (Institute for the Study of Labor (IZA), 2011)
This study provides a comparison of the size and value of unpaid family care work in two European member States, Italy and Poland. Using the Italian and Polish time use surveys, both the opportunity cost and the market replacement approaches are employed to separately estimate the value of family childcare and care of the elderly. The results show that, overall, in Italy the number of people performing family care work is higher, also due to the larger population. Italians participate somewhat less than Poles in child care, but substantially more in care of the elderly because of demographic factors. However, the huge difference in the value of unpaid family care work, which in Italy exceeds the value of Poland by about eight times, is largely to be attributed to the discrepancy in hourly earnings, average earnings of Poles being about one fifth of those of Italians. In GDP terms, instead, the value of unpaid family care work is more similar, ranging between 3.7 and 4.4 per cent of the Polish GDP and 4.1 and 5 per cent of the Italian GDP, depending on the estimation approach. The national values of these activities are discussed and an interpretation of the country differentials in the family care-taking gender gaps is given in terms of differences in culture, economic development and institutions.
urn:nbn:de:101:1-20110621308
Keywords: E01; E26; J13; J14; J16; J22; 330; unpaid work; time use; child care; care of the elderly; adult care; Poland; Italy; satellite accounts